Prospects for Mangrove Reforestation Using the Silvofishery Method in Aquaculture Areas in Bireuen Regency, Aceh - Shah Putra, Rima; Ernawita, Ernawita; Iswahyudi, Iswahyudi (Jurnal Akuakultur Indonesia, 2025)
The conflict between shrimp productivity and mangrove conservation can be addressed through the “silvofishery” pond model, which integrates shrimp farming with mangrove intercropping especially relevant for traditional pond farmers who dominate aquaculture in Indonesia. However, silvofishery is not yet widely practiced. This research aims to assess the understanding and acceptance of pond farmers in Bireuen Regency toward mangroves and silvofishery, and to identify barriers to future implementation. The study was conducted in three sub-districts Kuala, Peusangan, and Jangka using in-depth interviews with ten respondents selected through a snowball method. Quantitative responses were analyzed descriptively, while qualitative data were interpreted using Miles and Huberman’s interactive model. Findings reveal that mangrove reforestation in Bireuen is still under threat from land conversion. Silvofishery remains challenging due to three core issues: (1) declining per capita landholding makes it difficult for farmers to allocate pond space for mangrove planting; (2) not all farmers accept silvofishery without first seeing proven models initiated by the government; and (3) concerns about increased pests, such as crabs and birds, which are attracted to mangrove habitats. These factors contribute to the currently low prospects for mangrove rehabilitation through silvofishery at the farmer level. A paradigm shift is needed, encouraging farmers to see mangroves not as a threat but as allies in solving persistent aquaculture problems, including disease and water pollution. Policy support, field schools, and demonstration ponds will be critical in building local trust and fostering long-term ecological and economic resilience. Keywords: aquaculture, farmer perception, mangrove conservation, shrimp pond, silvofishery ABSTRAK Konflik antara produktivitas budidaya udang dan konservasi mangrove dapat diatasi melalui model tambak “silvofishery” yang mengintegrasikan budidaya udang dengan penanaman mangrove terutama relevan bagi petambak tradisional yang mendominasi sektor akuakultur di Indonesia. Namun, praktik silvofishery belum banyak diterapkan. Penelitian ini bertujuan untuk menilai pemahaman dan penerimaan petambak di Kabupaten Bireuen terhadap mangrove dan sistem silvofishery, serta mengidentifikasi hambatan implementasi ke depan. Studi dilakukan di tiga kecamatan Kuala, Peusangan, dan Jangka melalui wawancara mendalam terhadap sepuluh responden yang dipilih dengan metode bola salju. Data kuantitatif dianalisis secara deskriptif, sementara data kualitatif dianalisis menggunakan model interaktif Miles dan Huberman. Hasil menunjukkan bahwa rehabilitasi mangrove di Bireuen masih terancam oleh alih fungsi lahan. Silvofishery menghadapi tantangan karena tiga hal utama: (1) penyusutan luas lahan per kapita menyulitkan petambak untuk menyediakan ruang tanam mangrove di dalam tambak; (2) tidak semua petambak menerima konsep silvofishery tanpa melihat model nyata yang diinisiasi pemerintah; dan (3) kekhawatiran akan meningkatnya hama seperti kepiting dan burung yang tertarik ke habitat mangrove. Faktor-faktor ini menyebabkan prospek rehabilitasi mangrove melalui silvofishery masih rendah di tingkat petambak. Diperlukan pergeseran paradigma, agar petambak mulai melihat mangrove bukan sebagai ancaman, melainkan sebagai sekutu dalam mengatasi persoalan budidaya seperti penyakit dan pencemaran air. Dukungan kebijakan, sekolah lapang, dan tambak percontohan akan sangat penting untuk membangun kepercayaan lokal dan mewujudkan ketahanan ekologi dan ekonomi jangka panjang. Kata kunci: akuakultur, konservasi mangrove, persepsi petambak, tambak udang, wanamina